Hairy cell leukemia: A decade long experience of North Indian Hematology Center - Venkatesan Somasundaram; Abhishek Purohit; Mukul Aggarwal; Prabhu Manivannan; Pravas Mishra; Tulika Seth; Seema Tyagi; Manoranjan Mahapatra; Hara P Pati; Renu Saxena (Indian Journal of Medical and Paediatric Oncology)
Introduction: Hairy cell leukemia is a rare chronic B-cell disorder that follows an indolent but progressive course. This disorder is characterized by pancytopenia, splenomegaly, bone marrow fibrosis and the presence of atypical lymphoid cells with hairy projections in peripheral blood, bone marrow and spleen. Treatment is mainly with nucleoside analog cladribine, which induces complete remission in up to 85% cases. Materials and Methods: This is a retrospective analysis of Hairy cell Leukemia cases diagnosed and treated in the Department of Hematology, All India Institute of Medical Sciences, New Delhi between 2002 and 2013. Various parameters such as clinical features, laboratory parameters including complete blood cell count, bone marrow findings, cytochemistry, immunophenotyping by flowcytometry or immunohistochemistry, treatment protocol and complications secondary to treatment and relapse were reviewed. Results: A total of 35 cases were diagnosed during this period of 12 years of which 27 received cladribine and went in to remission. Median follow-up duration was 26 months. 5 (18%) cases had a relapse and all relapsed cases achieved second remission with cladribine; however, there was no case of second malignancy in our cohort. Conclusion: Cladribine has emerged as the treatment of choice for hairy cell leukemia given that the overwhelming majority of patients achieve long-lasting complete remissions. Upon relapse, these patients could be successfully salvaged with cladribine retreatment.